EFEKTIVITAS PELAYANAN KARTU TANDA PENDUDUK DI KECAMATAN JEBRES KOTA SURAKARTA - Neri Budiarto Mia; Suwardi, Sri Riris Sugiyarti (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2017)
EFEKTIVITAS PELAYANAN KARTU TANDA PENDUDUK DI KECAMATAN JEBRES KOTA SURAKARTAOleh :Neri Budiarto Mia, Dr.Drs, Suwardi, M.Si., Dra. Sri Riris Sugiyarti, M.Si. The purpose of this research is to know the effectiveness of the service of the identity card (KTP) in Subdistrict Jebres, Surakarta which refers to the 10 dimensions of quality improvement services according to Vincent and other ' (1997:2).The effectiveness showed in the perception of the user/community service with service providers in other words, If there are explosives in an understanding between what is done by the officer/service providers, with the results are perceived by the user/community service, then the service can be said to be effective. The effectiveness of the Ministry can be seen from the performance of the service providers that already produce good results, and the service quality perceived by users of the service.This research uses descriptive quantitative methods. Sampling techniques using incidental sampling, the sample consists of 50 service users/community service/provider and 6 officers. Data collection techniques in the study of using koesioner. The analysis used is servqual (sevice quality) with how to compare between the perception of the users with the perception of the service provider then there is a Gap, the less the service gap between the perceptions of users and service providers the effective services.The results of the ten indicators of the quality of service, timeliness of service have the score Gap (34.6) entered on the classification of "effective", the accuracy of the service have the score Gap (34.2) entered on the classification of "effective", the politeness and hospitality of attendants have the score Gap (39.2) entered on the classification of "highly effective", the officer has a responsibility score Gap (34.4) entered on the classification of "effective", discipline officers possesses score Gap (34.2) entered on the classification of "effective", ease of access services have the score Gap (35.6) entered on the classification of "highly effective", justice officials have the score Gap (34.4) entered on the classification of "effective", the speed of the officer having the score Gap (33.6) entered on the classification of "less effective", cleanliness and tidiness the Environment Ministry has a score Gap (34.4) entered on the classification of "effective", adequate supporting facilities have the score Gap (34.4) entered on the classification of "effective".From the results it can be concluded that the services the population Sign Cards (KTP) in Subdistrict Jebres cemetery city of Surakarta located on the category either, in other words the existing Services in district of Jebres cemetery city of Surakarta has reached the level of effectiveness. Key words: effectiveness, public service, Identity Card